2009
DOI: 10.1177/1099800408330849
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Secondhand Cigarette Smoke, Genetics, and Cervical Cancer: A Review of the Literature

Abstract: Research has suggested a link between smoking and cervical cancer; however, little data are available on secondhand smoke (SHS) exposure and cervical cancer risk. This article reviews the literature on the links among smoking, SHS exposure and cervical cancer. The review was based on a search of electronic databases. The research reviewed clearly showed that smoking increases cervical cancer risk through myriad mechanisms that interact with genetics and the pathologic processes leading to cervical cancer. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Genetic, host or environmental cofactors are related to the ability of HR-HPV to persist into the tissue with an increased risk to promote cancer development. Genetic polymorphisms, immune status and environmental carcinogens, among others, may indicate an increased risk of HR-HPV-mediated carcinogenesis [ 23 , 24 ].…”
Section: Origin Of Female Cancersmentioning
confidence: 99%
“…Genetic, host or environmental cofactors are related to the ability of HR-HPV to persist into the tissue with an increased risk to promote cancer development. Genetic polymorphisms, immune status and environmental carcinogens, among others, may indicate an increased risk of HR-HPV-mediated carcinogenesis [ 23 , 24 ].…”
Section: Origin Of Female Cancersmentioning
confidence: 99%
“…In recent years, with the increasing number of female smokers, smoking as one of the risk factors of cervical cancer ( Roura et al, 2014 ) was further studied. Some studies ( Pate et al, 2009 ; Su et al, 2018 ; Kim et al, 2021 ) showed that passive smoking also increased the risk of cervical cancer in females. In this study, the effect of current smoking on contraceptive use and cervical cancer can increase the risk of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that women who smoke have up to a five-fold increase in risk of cervical cancer [ 50 , 51 ] and presently 19.1% of women in the U.S. smoke [ 52 ]. Older women who were previous smokers and second hand smoke exposed are also at increased risk cervical dysplasia and therefore should be screened more carefully than those without other risk factors [ 53 ]. In addition, a genetic component identified in some women increases the risk of cervical cancer [ 54 ].…”
Section: Common Gynecologic Disorders In Older Womenmentioning
confidence: 99%
“…In addition, a genetic component identified in some women increases the risk of cervical cancer [ 54 ]. This link is likely enhanced by cigarette smoking [ 53 ]. Thus, women who smoke should be considered at higher risk for vulvar and vaginal cancers in addition to cervical cancers.…”
Section: Common Gynecologic Disorders In Older Womenmentioning
confidence: 99%